(untitled) (Fiep Bulletin - online, 2015)
It talks about the diffusion and the social impact of the knowledge in Physical Education and in sports sciences, from the periodical press, during 1930 and 2005. The main source was the Physical Education and Sport Periodical Catalogue (1930-2000). The results indicate the extinction of teaching and technical periodicals, the low impact of scientific periodicals and it also presents some suggestions for improving the availability and the accessibility to the produced and transmitted knowledge.